COMPARATIVE STUDY OF CONCRETE BEAMS CONVENTIONAL REINFORCING WEAPON AND CONCRETE BEAMS WOOD WEAPON OPPOSITIFOLIUS MALLOTUS - GIBIGAYE, ADAM MOHAMED (My University, 2023)
The objective of this work is to compare the mechanical performance of concrete beams reinforced with convention reinforcement (iron) and concrete beams reinforced with oppositifolius mallotus wood with a view to building an innovative construction system for habitable or non-habitable floors of pavilions in rural areas. For this fact, nine (09) specimens of section 10x10x40cm 3 were made at the rate of three (03) unreinforced concrete specimens; three (03) reinforced concrete with Mallotus oppositifolius wood (vegetable reinforcement) without prior treatment and three (03) reinforced concrete specimens of conventional reinforcement (iron) which were subjected to the four-point bending test after twenty-eight (28) of age. At the end of the tests, it was found that the oppositifolius mallotus wood frame improves the four-point bending strength of the beams compared to unreinforced beams without achieving the mechanical performance of reinforced beams in conventional reinforcement. We also note a lower arrow compared to unreinforced beams. A visual analysis of the beams reinforced with mallotus oppositifolius wood (plant frame) after a total rupture shows us a need to treat the surface of the mallotus oppositifolius wood to make it rougher in order to increase its adhesion with the concrete. We thus retain the possibility of using mallotus oppositifolius wood as a vegetal frame in the construction of social housing in rural areas after its waterproofing and treatment.
Keywords: Rural Areas; Mallotus Oppositifolius; Social Housing; Adhesion; Mechanical; Performance.